2022
DOI: 10.1523/jneurosci.2458-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

KL1 Domain of Longevity Factor Klotho Mimics the Metabolome of Cognitive Stimulation and Enhances Cognition in Young and Aging Mice

Abstract: Cognitive deficits are a major biomedical challenge-and engagement of the brain in stimulating tasks improves cognition in aged individuals (Wilson et al., 2002;Gates et al., 2011) and rodents (Aidil-Carvalho et al., 2017), through unknown mechanisms. Whether cognitive stimulation alters specific metabolic pathways in the brain is unknown. Understanding which metabolic processes are involved in cognitive stimulation is important because it could lead to pharmacologic intervention that promotes biological effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 56 publications
3
12
0
1
Order By: Relevance
“…For example, increasing the AP Beta-2-microglublin systemically has adverse effects on hippocampal-dependent cognitive functioning and neurogenesis (Smith et al, 2015). Conversely, a cleaved domain of the AP Klotho, KL1, was shown to be sufficient to enhance cognition and to mediate the effects of the complete protein (Gupta et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…For example, increasing the AP Beta-2-microglublin systemically has adverse effects on hippocampal-dependent cognitive functioning and neurogenesis (Smith et al, 2015). Conversely, a cleaved domain of the AP Klotho, KL1, was shown to be sufficient to enhance cognition and to mediate the effects of the complete protein (Gupta et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…GABA receptor agonist: Liu W, et al, 2021 ; Prud’homme et al, 2017a ; Son et al, 2019 ; Wang Q, et al, 2019 . Recombinant Klotho protein or peptides: Ali et al, 2020 ; Chen TH, et al, 2013 ; Doi et al, 2011 ; Gupta et al, 2022 ; Hu et al, 2017 ; Leon et al, 2017 ; Maltese et al, 2017 ; Mencke et al, 2017 ; Myung et al, 2022 ; Oh et al, 2018 ; Prud’homme et al, 2020 ; Rao Z, et al, 2019 ; Takenaka et al, 2018 , 2019 , 2020 ; Yang et al, 2015 ; Yuan et al, 2022 ; Zhong et al, 2020 . Gene therapy: Arbel Rubinstein et al, 2021 ; Franco et al, 2021 ; Lin & Sun, 2015a , b ; Ni et al, 2021 ; Mencke et al, 2017 ; Shin et al, 2019 ; Xiang et al, 2021 ; Zeng et al, 2019 .…”
Section: Approaches To Klotho-based Therapyunclassified
“…In young and aged mice, systemic delivery of a Klotho-derived peptide that does not cross the BBB improved cognition and reduced neurodegenerative pathology ( Leon et al, 2017 ). Others showed that systemic delivery of either s-Klotho or only the KL1 domain also improved cognition ( Gupta et al, 2022 ). It is unclear how these beneficial Klotho-based effects are mediated, but penetrance into the brain does not appear to be required, and this merits further investigation.…”
Section: Approaches To Klotho-based Therapymentioning
confidence: 99%
“…Testing was carried out as described [12,[21][22][23]. Briefly, the water maze pool (diameter, 122 cm) contained white, opaque water with a square, 14 cm 2 platform submerged 2 cm below the surface.…”
Section: Morris Water-mazementioning
confidence: 99%